Program Pembiayaan Pemerintah dalam Upaya Mendukung Produksi Kentang di Kabupaten Garut, Jawa Barat - Eliana Wulandari; . Ernah; Dika Supyandi (Institut Pertanian Bogor, 2018)
Finance can be accessed from various financial providers, for instance finance from government. One of the financial forms provided by the government is in-kind finance such as seeds, fertilizer, and harvesting tools. The objective of this study was to analyze the relationship betwen agricultural production and in-kind finance from Indonesian government. The study was conducted from May to September 2017 using survey technique to collect data from 97 potato farmers in Garut District. The data were analyzed using descriptive statistics technique and Ordinary Least Square regression. Results showed that in-kind finance from the government helped farmers in potato production. Farmers who had access to in-kind finance from the government had a higher potato production compared to farmers who did not have access to the in-kind finance.